An overview of recent advancements in fibre-reinforced 3D printing concrete - Zhou, Yi; Althoey, Fadi; Alotaibi, Badr Saad; Gamil, Yaser; Iftikhar, Bawar (Frontiers in Materials, 2023)
3D printing, also known as additive manufacturing, has recently gained significant attention and popularity as a transformative technology across various industries. One area where 3D printing is making remarkable strides is in the construction field, particularly with the emergence of 3D printing concrete (3DPC). While 3DPC holds immense promise, there are still challenges to overcome, such as incorporating reinforcement. This study reviews the potential of using fibre reinforcement to overcome the challenge of making ductile concrete for 3D printing that can withstand substantial tensile stresses. Effects of various types of fibre addition on widespread aspects of 3DPC are systematically reviewed. This review study considers various aspects of 3DPC: rheological characteristics, buildability, anisotropic mechanical behavior, and ductility. These characteristics of fibre-reinforced 3DPC are discussed in light of the published literature. This research’s graphical and statistical visualizations offer valuable insights for academic scholars. This review summarizes recent advancements in fibre-reinforced 3DPC while highlighting the persisting challenges in developing fibre-reinforced 3DPC with desired properties for real-world applications.